Suitability of NaI complexed sodium alginate-polyvinyl alcohol biodegradable polymer blend electrolytes for electrochemical device applications: Insights into dielectric relaxations and scaling studies - Cyriac, Vipin; Ismayil; Mishra, Kuldeep; Sudhakar, Y.N.; Rojudi, Z.E.; Masti, Saraswati P.; Noor, I.M. (Elsevier, 2024)
This study focuses on an in-depth analysis of the relaxation phenomenon of sodium iodide (NaI)-complexed solid polymer electrolyte membranes based on sodium alginate (NaAlg) and poly (vinyl alcohol) (PVA) using various formalisms to test the suitability of these membranes for electrochemical device applications. The incorporation of NaI led to an increase in the ionic conductivity from (6.12 ± 0.14) × 10−8 Scm−1 (PNI0, pure blend) to (4.27 ± 0.09) × 10−6 (PNI10, 10 wt% of NaI). Deep insights into ion transport parameters at ambient and high temperatures, obtained from Nyquist plot fitting revealed the dependency of dc conductivity on carrier concentration (n) rather than mobility (μ) and diffusion coefficient (D). Scaling studies based on AC conductivity and tangent loss revealed the collapse of conductivity and tangent loss plots into a single master curve, implying that the optimum sample obeys time-temperature superposition principle (TTSP). The temperature dependence of the Jonscher's exponent indicates that the conduction mechanism can be effectively represented by the Quantum Mechanical Tunneling model (QMT). The non-Debye behavior exhibited by the samples can be elucidated through the electric modulus formalism and confirmed dielectric properties of the electrolytes, as demonstrated by the incomplete semicircular arcs observed in the Argand plots. Moreover, the prepared samples were completely biodegradable, indicating the eco-friendly nature of the electrolytes.